Dampak Terpasangnya Portal di Hutan RPH Kanar Luk KPH Puncak Ngengas Batulanteh, Sumbawa NTB - Dian Diniyati; Budiman Achmad (Balai Litbang Teknologi Agroforestry, Ciamis, 2020)
One of the efforts of residenresidents' efforts in the Kanar Luk RPH forest area was mining the sandstone from the Bangkong River, which potentially threatenpotentially threatening environmental sustainability and community safety, t. Therefore the portal installation policy was enforced by the Forest Management Unit (FMU). The research aimed to outline elaborate the impact of portal installation for condition of stakeholder socioeconomic and condition ofon the condition of stakeholder socioeconomic and environment. This activity was conducted on August 2015 and July 2019 at RPH Kanar Luk in the KPH Puncak Ngegas Batulanteh area. Data were collected through an interview to with 29 residents, 2 two RPH officers, 2 two shop owners, 1 one truck driver, and 1one KPH officer, b. Besides that, it was also conducted by FGD and observationFGD and observation were also conducted. The collected data had been analyzed quantitatively. The result revealed that residents no longer did mining sandstone activity but now more focus to takewere now more focused on taking care of agricultural plants. Livestock were was maintained so that there was no more conflict. The movement of people entering the area were was limited, ; the security of the area was better maintained and had an impact onarea's security was better maintained and impacted the comfort of the people who lived in the area. The river water condition was getting normal because no more floods that inundate Bronjong Village. The existence of a portal can certainly reduce residents' income, this condition therefore. Therefore, this condition needed efforts to foster a business culture in the community, including the culture of cashew nut processing and honey bee cultivation, because the raw materials around the research location were abundant